The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jcae.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Institutional factors and conditional conservatism in Malaysia: Does international financial reporting standards convergence matter?

Abstract: We examine the impact of International Financial Reporting Standards (IFRS) convergence on conditional conservatism in Malaysia. In addition, we examine the influence of various institutional factors, namely, political connections, Bumiputras directors, family firms and richest-men connections on conservatism. Prior literature presents evidence of IFRS convergence on conservatism, but limited evidence exists on the role of institutional factors on conservatism. Using a sample of 1760 firm-year observations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
17
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 90 publications
5
17
1
2
Order By: Relevance
“…For ownership structure, we added politician ownership (PCOWN) as control variable. Prior studies have suggested that politician-owned firms are less likely to implement conservative financial reporting due to lenders being less concerned with downside default risk and protection from public scrutiny [67][68][69]. In addition, we controlled for the ownership of outside shareholders (OUTOWN) and institutional shareholders (INST), since external monitoring mechanisms could exhibit a higher degree of accounting conservatism [70].…”
Section: Methodology Of Testing Modelmentioning
confidence: 99%
“…For ownership structure, we added politician ownership (PCOWN) as control variable. Prior studies have suggested that politician-owned firms are less likely to implement conservative financial reporting due to lenders being less concerned with downside default risk and protection from public scrutiny [67][68][69]. In addition, we controlled for the ownership of outside shareholders (OUTOWN) and institutional shareholders (INST), since external monitoring mechanisms could exhibit a higher degree of accounting conservatism [70].…”
Section: Methodology Of Testing Modelmentioning
confidence: 99%
“…We posit that the latter view is applicable in the setting of our studies. Prior studies have explored the characteristics of politically connected firms worldwide (Faccio, 2010) and their effect on the capital market in relation to corporate transparency (Bushman et al, 2004), firm performance (Fisman, 2001;Johnson & Mitton, 2003), Wahab, 2016), and earnings quality (Chaney et al, 2011). Gul (2006) examines the impact of political connections on audit fees in Malaysia, and finds that auditors view connected firms as riskier, which results in higher audit fees.…”
Section: Political Connections and Tax Aggressivenessmentioning
confidence: 99%
“…However, very little studies have been carried out in developing countries, which provide a different setting due to differences in economic environments, rules and regulation as well as accounting standards. For example, Malaysia as a developing country, where majority of firms are family firm (Haji-Abdullah, Marini & Keshab 2016) and very conservative (Marzuki & Wahab 2017) compare to other developing countries provides an alternative setting to study this issue.…”
Section: Introductionmentioning
confidence: 99%